ChemInform Abstract: Mild Cobalt‐Catalyzed Negishi Cross‐Couplings of (Hetero)arylzinc Reagents with (Hetero)aryl Halides. Issue 28 (June 2016) - Haas, Diana; Hammann, Jeffrey M.; Lutter, Ferdinand H.; Knochel, Paul
Abstract: This cobalt‐catalyzed, sodium formate promoted reaction enables the cross‐coupling of N‐heterocyclic chlorides and bromides as well as aromatic halogenated ketones with both electron‐rich and ‐poor arylzinc reagents.